2017
DOI: 10.1002/2016ja023607
|View full text |Cite
|
Sign up to set email alerts
|

Bounce resonance scattering of radiation belt electrons by H+ band EMIC waves

Abstract: We perform a detailed analysis of bounce‐resonant pitch angle scattering of radiation belt electrons due to electromagnetic ion cyclotron (EMIC) waves. It is found that EMIC waves can resonate with near‐equatorially mirroring electrons over a wide range of L shells and energies. H+ band EMIC waves efficiently scatter radiation belt electrons of energy >100 keV from near 90° pitch angles to lower pitch angles where the cyclotron resonance mechanism can take over to further diffuse electrons into the loss cone. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 42 publications
1
64
2
Order By: Relevance
“…As a commonly observed wave mode in the Earth's magnetosphere, electromagnetic ion cyclotron (EMIC) waves are excited by a temperature anisotropy of 1–100 keV ions (Anderson et al, ; Chen et al, ; Cornwall, ; Wang et al, ; Zhang et al, ) and propagate in three distinct frequency bands (H + , He + , and O + ) separated by the corresponding ion gyrofrequencies. EMIC waves have long been recognized to account for the efficient precipitation loss of outer belt relativistic electrons (e.g., Cao, Ni, et al, ; Cao, Yuri, et al, ; Kersten et al, ; Liu et al, ; Meredith et al, ; Miyoshi et al, ; Ni et al, ; Rodger et al, ; Shprits et al, , ; Summers & Thorne, ; Usanova et al, ; Zhang et al, ), while the resonant interactions between EMIC waves and protons can take place over a very broad spatial range in the magnetosphere. Xiao et al () proposed that EMIC waves in the magnetospheric cusp can efficiently scatter protons into the atmosphere and produce the cusp proton aurora.…”
Section: Introductionmentioning
confidence: 99%
“…As a commonly observed wave mode in the Earth's magnetosphere, electromagnetic ion cyclotron (EMIC) waves are excited by a temperature anisotropy of 1–100 keV ions (Anderson et al, ; Chen et al, ; Cornwall, ; Wang et al, ; Zhang et al, ) and propagate in three distinct frequency bands (H + , He + , and O + ) separated by the corresponding ion gyrofrequencies. EMIC waves have long been recognized to account for the efficient precipitation loss of outer belt relativistic electrons (e.g., Cao, Ni, et al, ; Cao, Yuri, et al, ; Kersten et al, ; Liu et al, ; Meredith et al, ; Miyoshi et al, ; Ni et al, ; Rodger et al, ; Shprits et al, , ; Summers & Thorne, ; Usanova et al, ; Zhang et al, ), while the resonant interactions between EMIC waves and protons can take place over a very broad spatial range in the magnetosphere. Xiao et al () proposed that EMIC waves in the magnetospheric cusp can efficiently scatter protons into the atmosphere and produce the cusp proton aurora.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that low‐frequency hiss could bounce resonate efficiently with near‐equatorially mirroring electrons at energies ranging from 10 keV to 10 MeV. The scattering efficiency at L = 5 is found to be much stronger than that at L = 4 and 4.5, which is mainly due to the stronger hiss wave spectral intensities (as shown in Figure ) and lower geomagnetic field intensity at L = 5 (Cao et al, ; Tao & Li, ). Figure illustrates that the bounce resonant pitch angle scattering rates have a pronounced dependence on the electron equatorial pitch angle α eq .…”
Section: Numerical Resultsmentioning
confidence: 97%
“…The resonance condition for bounce resonant wave‐particle interactions can be written as follows (e.g., Cao et al, ; Roberts & Schulz, ; Shprits, , ): f=0.5eml0.25emfb, where f is the wave frequency (in Hz), l is the bounce resonance order, f b = βc /(4 LR E T ( α eq )) is the particle bounce frequency, β = v / c , v is the velocity of particle, c is the velocity of light, L is the McIlwain L shell value, R E is the Earth's radius, and T()αeq=1.38020.31987()sin()αeq+sin()αeq.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation belt electrons can undergo pitch angle scattering through interactions with various wave modes, including whistler mode chorus, plasmaspheric hiss, magnetosonic waves, and electromagnetic ion cyclotron waves (e.g., Cao, Ni, Summers, Bortnik, et al, 2017;Ni et al, 2013Ni et al, , 2015Ni et al, , 2017Ni, Zou, et al, 2018;Summers et al, 2007aSummers et al, , 2007bThorne, 2010). In particular, as an important physical process in the inner magnetosphere, plasmaspheric hiss is a typically structureless, broadband, and naturally occurring whistler mode emission generally confined within the dense plasmasphere and high-density plasmaspheric plumes (e.g., Carpenter et al, 1993;Chappell, 1974;Laakso et al, 2015;Su et al, 2018;Thorne, 2010), while the fine structure of plasmaspheric hiss has been observed by Van Allen Probes, as recently reported by Summers et al (2014).…”
Section: Introductionmentioning
confidence: 99%